(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
This article discusses the creative process of the performance of the Odisseia dos sentidos, a circus show that debuted in 2011 and has been reassembled several times to finally constitute a big juggling show of lights and fire. The descriptive analysis exposes the point of view of two artists about a circus creation process, and focus in the object manipulation technique. In the first moment, the work was predominantly performative character, but later it received new aesthetic nuances, in a process of collective direction and construction, which allowed the creation of an dramaturgy that showed the point of view of artists and the public that watched the presentations in different cities in Bahia, Brazil and Europe.